Evaluasi Implementasi SISKEUDES ( Sistem Keuangan Desa ) Online di Kabupaten Pati Pada tahun 2018-2020 - Kresna Aru Wijayandanu; Puji - Astuti (Journal of Politic and Government Studies, 2020)
The Village Financial System application or SISKEUDES Online is an application that makes it easier for village governments to manage village finances. Pati District implements the SISKEUDES application, with the aim of making village financial management more transparent, accountable and accountable in accordance with applicable regulations. Pati District is one of the districts in Indonesia that has succeeded in implementing SISKEUDES Online simultaneously in all villages (401 villages) in Pati District. The purpose of this research is to describe more deeply about the Evaluation of the Implementation of the SISKEUDES Online Application in Pati Regency 2018-2020. This research uses descriptive qualitative research methods with data collection techniques through interviews, and documentation studies conducted on related informants.The results of this research are to describe the various findings in the field related to the Implementation of the SISKEUDES Online Application in Pati District, namely by providing communicative, consistent, and clear Technical Guidance to all operators and related OPDs in using the SISKEUDES Online application, the commitment of the Pati District Government in carrying out the assistance function to villages in terms of procurement of facilities and infrastructure to support the implementation of the SISKEUDES application, as well as the integrity of the Pati District Government with OPD and related agencies in a bureaucratic and well-structured manner. For this reason, it is necessary to evaluate the process in evaluating the implementation of SISKEUDES (Village Financial System) Online in Pati District. In the implementation process, several factors were still found to be obstacles, but in technical practice all villages in Pati District have carried out the implementation process starting from planning to accountability that is relevant in accordance with applicable regulations and in running the application it is well structured.